The Principles Underlying What is Communicated and not Said: A Cursory Discussion of Grice’s Cooperative Principle and its Maxims - Yeboah, Joyce (Journal of English Language Teaching and Applied Linguistics, 2021)
As humans communicate, much of what goes on is not simply about conveying information to themselves. In Grice’s paper “Logic and Conversation (1975)”, he argued that some cooperative principle is assumed to be in operation for a person to interpret what someone else says. In a typical conversational flow, the speaker needs to adhere to a pattern in order to be informative, truthful and clear and there exist a set of principles that direct the hearer to a particular interpretation of what is said. This is because a speaker can mean something either by saying it or by saying (or ‘making as if to say’) something else. What is implicated by saying something is generally not what is said. This paper attempted to critically review how speakers manage to convey more than what is said and how the hearer arrives at the speaker meaning using a descriptive qualitative approach. This paper employs a descriptive qualitative approach. The key findings of the study is described in two context: first of all, speakers intentionally obey the maxims in conversation which in essence affirms Grice’s theory of cooperative principle in fulfilment of at least some of the maxims. Second, speakers exploit the maxims either deliberately or fail to observe by deciding to violate, suspend, flout, infringe, or opt-out of a conversation. This situation is one premised to give rise to conversational implicatures. A competent hearer should be able to arrive at these possible conclusions in order to draw out the speaker meaning from what was merely said.